2011
DOI: 10.5194/acp-11-1879-2011
|View full text |Cite
|
Sign up to set email alerts
|

Radiative impact of mineral dust on monsoon precipitation variability over West Africa

Abstract: Abstract. The radiative forcing of dust and its impact on precipitation over the West Africa monsoon (WAM) region is simulated using a coupled meteorology and aerosol/chemistry model (WRF-Chem). During the monsoon season, dust is a dominant contributor to aerosol optical depth (AOD) over West Africa. In the control simulation, on 24-h domain average, dust has a cooling effect (−6.11 W m −2 ) at the surface, a warming effect (6.94 W m −2 ) in the atmosphere, and a relatively small TOA forcing (0.83 W m −2 ). Du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
214
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(235 citation statements)
references
References 55 publications
13
214
2
Order By: Relevance
“…Several studies employing WRF-Chem reveal that aerosols reduce downward solar radiation reaching the ground, inhibit convection, reduce the PBL (planetary boundary layer) and, hence, make the lower atmosphere more stable (Fan et al, 2008;Forkel et al, 2012;Zhang et al, 2010). WRF-Chem results also indicate that aerosols can modify atmospheric circulation systems, resulting in changes in monsoon strength, precipitation distribution, and midlatitude cyclones (Zhao et al, 2011(Zhao et al, , 2012.…”
Section: B Zhang Et Al: Simulating Aerosol-radiation-cloud Feedbacksmentioning
confidence: 86%
“…Several studies employing WRF-Chem reveal that aerosols reduce downward solar radiation reaching the ground, inhibit convection, reduce the PBL (planetary boundary layer) and, hence, make the lower atmosphere more stable (Fan et al, 2008;Forkel et al, 2012;Zhang et al, 2010). WRF-Chem results also indicate that aerosols can modify atmospheric circulation systems, resulting in changes in monsoon strength, precipitation distribution, and midlatitude cyclones (Zhao et al, 2011(Zhao et al, , 2012.…”
Section: B Zhang Et Al: Simulating Aerosol-radiation-cloud Feedbacksmentioning
confidence: 86%
“…At night, an opposite tendency is recorded and the RADON SH fluxes are higher by up to 2 W m −2 than the corresponding fluxes based on the RADOFF configuration of the model. The reverse effects on SH levels, over the western parts of the Sahara, between day-time and night-time as well as the diurnal variability of their magnitude have been pointed out by Zhao et al (2011). Based on the paired t test, the differences between RADOFF and RADON SH values are statistically significant at 95 % confidence level throughout the forecast period.…”
Section: Impact On Sensible and Latent Heat Fluxesmentioning
confidence: 94%
“…However, several studies have shown that dust can play an important role in the changes of Sahel climate (e.g., Nicholson, 2000;Prospero and Lamb, 2003;Yoshioka and Mahowald, 2007;Kim et al, 2010;Zhao et al, 2011). Dust particles play a fundamental role in the energy balance of the Earth-atmospheric system due to their high emission rate (Andreae, 1995;Satheesh and Moorthy, 2005;IPCC, 2007), entering the atmosphere through wind erosion of dry soils.…”
Section: Aerosolsmentioning
confidence: 99%